ADVANCED MOLECULAR AND CELL BASED THERAPIES FOR ATHEROSCLEROSIS - SB, MAHAMMAD RAHMATHULLA; K, LAKSHMI DEVI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Cardiovascular disease (CVD) is the most frequent cause of premature death in modern industrialized countries, accounting for 4.35 million deaths each year in Europe, and 35% of deaths in the United Kingdom. Atherosclerosis is pathological process characterized by formation of subintimal plaques that can reduce or obstruct blood flow through the vessel. It is a result of normal blood vessels ageing, with initial lesion developing before age 30 (so-called fatty streaks). Risk factors that significantly accelerate this process are serum lipid impairment, hypertension, cigarette smoking, diabetes mellitus, obesity, physical inactivity and hereditary factors i.e. positive family history of cardiovascular disorders. . Compelling experimental and clinical evidence has demonstrated that both systemic and local inflammation might play a prominent role in the pathogenesis of atherosclerosis and its clinical complications. Since inflammatory processes accompany all stages of atherosclerosis, measurement of plasma/serum concentrations of circulating inflammatory biomarkers might aid in identifying individuals at high risk for cardiovascular disease (CVD). Currently employed treatment strategies include risk factor modification, conventional pharmacotherapy, and percutaneous or surgical revascularization. Yet despite these interventions disease progression often results in recurrent symptoms, with many patients exhausting all therapeutic options. KEY WORDS: Atherosclerosis, Risk Factors, Pathophysiology, Inflammation. Biomarkers for Atherosclerosis, Polyphenols, Molecular and Cell Based Therapies